An empire in eclipse : - Welfield, John (Athlone Press, 1988)
This book examines Japanese politics and diplomacy during the years extending from the disintegration of the Greater East Asia Co-prosperity Sphere in 1944 - 45, through the occupation and the Cold War until the collapse of the American-Soviet detente in 1978.